The Liouville Type Theorem for a System of Nonlinear Integral Equations on Exterior Domain (Journal of Partial Differential Equations, 2019)
"In this paper we are concerned with a system of nonlinear integral equations\r on the exterior domain under the suitable boundary conditions. Through the method\r of moving planes in integral forms which has some innovative ideas we obtain that\r the exterior domain is radial symmetry and a pair of positive solutions of the system\r is radial symmetry and monotone non-decreasing. Consequently, we can obtain the\r corresponding Liouville type theorem about the solutions."
Keywords: System of integral equations; exterior domain; symmetry; monotonicity; Liouville type theorem.